The Object-Z Specification Language - Smith, Graeme (Springer US, 2000)
Object-Z is an object-oriented extension of the formal specification language Z. It adds to Z notions of classes and objects, and inheritance and polymorphism. By extending Z's semantic basis, it enables the specification of systems as collections of independent objects in which self and mutual referencing are possible. The Object-Z Specification Language presents a comprehensive description of Object-Z including discussions of semantic issues, definitions of all language constructs, type rules and other rules of usage, specification guidelines, and a full concrete syntax. It will enable you to confidently construct Object-Z specifications and is intended as a reference manual to keep by your side as you use and learn to use Object-Z. The Object-Z Specification Language is suitable as a textbook or as a secondary text for a graduate-level course, and as a reference for researchers and practitioners in industry
Keywords: Artificial Intelligence; Programming Languages, Compilers, Interpreters; Software Engineering/Programming and Operating Systems; Computer Science, general; Artificial intelligence; Programming languages (Electronic computers); Software engineering; Computer science; Objektorientierte Programmiersprache; Z -- Programmiersprache